2022
DOI: 10.1021/acsami.2c07869
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Hydroxyapatite Coating Infiltrated with a Graphene Oxide Hybrid Supramolecular Hydrogel Orchestrates Antibacterial and Self-Lubricating Performance

Abstract: Hydroxyapatite (HA) bioceramic coating has been extensively applied for the modification of metallic implants to improve their biocompatibility and service life after implantation. Unfortunately, HA coating often suffers from high friction, severe wear, and bacterial invasion, which restrict its application in artificial joints. According to a bioinspired soft/hard combination strategy, a novel HA composite coating that is infiltrated with a vancomycin-loaded graphene oxide (GO) hybrid supramolecular hydrogel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…The main mechanisms of synergetic performance improvement were as follows: 1) Texture grooves could store lubricating materials and continuously supply them to the interface of the friction pair, so that the lubricating transfer film could maintain for a longer time. [ 39 ] 2) Textures could improve the adhesion between the lubricant coating and substrate. [ 40 ] However, the results showed that only the L2 texture and solid lubricant coating synergistically improved the tribological properties of the substrate.…”
Section: Resultsmentioning
confidence: 99%
“…The main mechanisms of synergetic performance improvement were as follows: 1) Texture grooves could store lubricating materials and continuously supply them to the interface of the friction pair, so that the lubricating transfer film could maintain for a longer time. [ 39 ] 2) Textures could improve the adhesion between the lubricant coating and substrate. [ 40 ] However, the results showed that only the L2 texture and solid lubricant coating synergistically improved the tribological properties of the substrate.…”
Section: Resultsmentioning
confidence: 99%
“…In a 15% texture ratio, the T-shaped network texture’s friction coefficient drops to 0.077, a 38% reduction from the original surface [ 250 ]. Self-lubricating artificial joints benefit from this strategy for friction reduction [ 254 , 255 , 256 , 257 ]. Therefore, the Y-shaped network has been recommended to improve friction/tribological performance.…”
Section: Biomimetic Surfaces Inspired By Plantsmentioning
confidence: 99%
“…6−8 Many gel materials have good and interesting elastic properties and can deform their shapes smoothly without disrupting their chemical structures. 9 Thus, these materials are expected to be used in various applications such as coating reagents, 10,11 soft actuators, 12,13 soft robotics, 14,15 soft sensors, 16 and artificial biomaterials. 17,18 To date, researchers have attempted to create various functional gel materials to use in the above applications.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Gel materials , consist of solvents and three-dimensional polymeric networks formed from low-molecular-weight molecules or polymers. Many gel materials have good and interesting elastic properties and can deform their shapes smoothly without disrupting their chemical structures . Thus, these materials are expected to be used in various applications such as coating reagents, , soft actuators, , soft robotics, , soft sensors, and artificial biomaterials. , To date, researchers have attempted to create various functional gel materials to use in the above applications. For example, gel materials that shrink and expand depending on time based on the Belousov–Zhabotinsky (BZ) reaction have been reported. , These gel materials oscillate like a heartbeat.…”
Section: Introductionmentioning
confidence: 99%